First year nursing students University of Sultan Zainal Abidin responses to test anxiety inventory - Farrahdilla, Hamzah; Vidya, Bhagat; Haszalina, Hassan; Khairi, Che Mat; Safiya, Amaran (2018)
Test anxiety also stated to exam anxiety that a worry about sitting for an examination. This situation affects students physically, emotionally and cognitively. This study examined first year nursing students’ response to Test Anxiety Inventory. This study applied cross sectional study design. Sixty students were participated in the study. Participants’ response to Test Anxiety Inventory was developed by Spielberger et.al. (1980). Test Anxiety Inventory has two major components; worry and emotionality. The data was analysed using SPSS statistics Version 22 (IBM Co., Armonk, NY, USA). Descriptive analysis was used for descriptive data; prevalence, percentage and mean score. The total mean score of test anxiety is 53.59 (12.36), worry 22.28 (3.61) and emotionality 22.80 (3.54). Based on this classification, only (1) 1.7% respondents no anxiety, (22) 36.7% respondents experienced of mild anxiety, more than half (35) 58.3% respondents had moderate anxiety and (2) 3.3% respondents experienced of severe anxiety. Majority first year nursing students were under test anxiety. The implication of this study is giving overview of mind- body interventions to reduce anxiety during exam. The faculty, lecturer or advisor should find out the main factors contribute to test anxiety. The used of coping strategies like mind-body therapy might benefit for students.